Sorbitol immersion controls chilling injury in CA stored ‘Palmer’ mangoes - Sanches, Alex Guimarães [UNESP]; Silva, Maryelle Barros da [UNESP]; Wong, María Carolina Casares [UNESP]; Oliveira, Antonio Rafael Gomes de; Pedrosa, Vanessa Maria Dantas [UNESP]; Fernandes, Thiago Feliph Silva [UNESP]; Gratão, Priscila Lupino [UNESP]; Teixeira, Gustavo Henrique de Almeida [UNESP] (Elsevier, 2022)
Chilling injury (CI) in mangoes can be reduced using a controlled atmosphere (CA) and sorbitol immersion, although studies combining these treatments have yet to be recorded. Therefore, the objective of this study was to use multivariate analysis to evaluate the effectiveness of these methods in controlling CI. ‘Palmer’ mangoes were immersed in 0.1 and 2.5 % (w/v) sorbitol solutions and stored under CA (5 % O2 + 5 % CO2) at 8 °C for 30 d. The evaluations were performed under CA storage conditions (0, 10, 20, and 30 d), after which the fruit were transferred to an ambient temperature environment (∼23 °C) for a further 7 days. CI was minimized in mangoes treated with 2.5 % sorbitol and stored in a CA. In addition, the physicochemical variables (soluble solids content, titratable acidity, SSC/TA ratio, and pH), firmness, and mesocarp color (L*, hº, and C*) were not affected. CI development was associated with increased fresh weight loss and epicarp color (L*, hº, and C*). Hydrogen peroxide (H2O2) levels were related to CI symptom development, which intensified with the transfer to an ambient temperature, mainly due to increased electrolyte leakage (EL), lipid peroxidation (LP), and polyphenol oxidase (PPO) activity. CI inhibition in mangoes treated with 2.5 % sorbitol under a CA was related to the non-enzymatic (vitamin C and total polyphenols) and enzymatic (superoxide dismutase – SOD, catalase – CAT, and ascorbate peroxidase – APX) defense metabolisms, allowing for the quality of the fruit to be maintained for up to 30 d at 8 °C.
Keywords: Enzymatic metabolism; Mangifera indica L.; Non-enzymatic metabolism; Physiological disorder; Principal component analysis